2005
DOI: 10.1093/jnci/dji340
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Transcription Factor E2F1 and Telomerase in Glioblastomas: Mechanistic Linkage and Prognostic Significance

Abstract: E2F1 may participate in telomerase activity regulation in malignant glioma cells. Its expression appears to be strongly associated with the survival of patients with malignant brain tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
49
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 51 publications
5
49
0
2
Order By: Relevance
“…In gliomas, for instance, it has been reported an almost universal dysfunction of the Rb pathway (3), with the ultimate increase in E2F1 transcriptional function (12). Our group has recently reported the presence of E2F1 overexpression in malignant gliomas and its value as a prognostic of survival (13). In this study presented here, we investigated the role of E2F1 in the development and maintenance of brain cancer using a transgenic mouse model engineered to express E2F1 within glial cells and/or neural precursor cells (GFAP-tgE2F1).…”
Section: Introductionmentioning
confidence: 84%
“…In gliomas, for instance, it has been reported an almost universal dysfunction of the Rb pathway (3), with the ultimate increase in E2F1 transcriptional function (12). Our group has recently reported the presence of E2F1 overexpression in malignant gliomas and its value as a prognostic of survival (13). In this study presented here, we investigated the role of E2F1 in the development and maintenance of brain cancer using a transgenic mouse model engineered to express E2F1 within glial cells and/or neural precursor cells (GFAP-tgE2F1).…”
Section: Introductionmentioning
confidence: 84%
“…Indeed, increased expression of cyclins and downregulation of CDKIs, including p27Kip1 and p16Ink4a/p19Arf, have been described in gliomas (Tamiya et al, 2001;Alonso et al, 2005;Arifin et al, 2006), but altered expression of Rb (which is likely associated with increased bioavailability of nuclear E2F1) has been associated with worse prognosis (Hilton et al, 2004). Our data suggest an important role of E2F1 in the transition between proliferation and differentiation of OPC and reveal the existence of an HDAC1-dependent switch during the downregulation of critical E2F1 targets, such as Uhrf1.…”
Section: Discussionmentioning
confidence: 99%
“…The ICOVIR model is based on the potential of E2F1 promoter for autoregulation by E2F1 protein. Importantly, our group has previously shown that E2F1 is overexpressed in malignant gliomas and that E2F overexpression is strongly associated with a poor prognosis in patients with high-grade gliomas (33). In light of these results, the correlation between E2F1 free activity and ICOVIR-5-mediated oncolytic effect is significant.…”
Section: Discussionmentioning
confidence: 80%